Ensino a Distância: Uma análise do design de um curso de Cálculo com um olhar no conteúdo de limites e continuidade de uma variável real - Forster, Sandra Regina Leme (2007)
The aim of this study is to present the material developed to the contents of Limit a Continuity of Functions of a Real Variable (Limite e Continuidade de Funções de uma Variável Real); demonstrate the analysis of the production of the applicable methodologies for the subject Differential and Integral Calculus II (Cálculo Diferencial e Integral II), one of the units required by the undergraduate academic degree in Bachelor of Mathematics, a program developed in a distance learning basis held by a university in São Paulo; as well as present suggestions to improve the course mentioned above. The theoretical base built in this paper was founded in two theories: the Semiotic Representation Registers Theory, by Raymond Duval, used in researches related to knowledge acquisition and organizing learning situations, and the Interactionist Theory, which is rooted in the studies of Piaget and Vygotsky, authors that forego the distance learning programs. This theory has been interpreted and rewritten by authors that work with distance learning programs and state that interaction promotes learning in any educational environment. This study also exposes what the researcher understands by distance learning and the media used in this kind of learning program. This paper consists of a methodology research based in design where quantitative and qualitative analyses were used, especially, the triangular analysis of data collected through observations of several natures. The results obtained through this research show that: the material and the methodologies applied to the course were well accepted, however, the students prefer the printed material. The students that frequently interacted during the course had better learning results. The development of activities with different types of semiotic representation registers provoke questioning, aid the learning of mathematics concepts and allow to observe if the concept was acquired by the student. The material developed to Continuity teaching was not sufficient to promote learning and must be reorganized